Micropalaeontological data from NEP1, NEP2, NEP3, Nördlingen, southern Germany - Ella Quante; Ema Zvara; Snježana Pejdanović; Diego Volosky; Peter Kühn; Lukas Werther; Christoph Zielhofer; Peter Frenzel (PANGAEA, 2025)
Three soil profiles from the Eger floodplain in Nördlingen in southern Germany (NEP1, NEP2 and NEP3), were sampled and micropalaeontological data were collected. Samples were weighted, wet sieved through 125 μm, dried on a heating plate at <60°C, and studied under a stereomicroscope at the University of Jena, Germany. Some specific particles of interest (plant remains, charcoal, mollusc and brick fragments) were assessed in semiquantitative abundance classes for each sample, while all other particles of interest were picked and counted in absolute abundances. This includes Mollusca, Ostracoda, reworked microfossils, macrobotanical remains (seeds and fruits), and insect and bone fragments. Where possible, taxa were identified down to species level. The data allow to develop a palaeoenvironmental reconstruction through the soil profiles, and can provide information on fluvial activity, landscape development and the general hydrological situation through time. It can in combination with other data corroborate the correlation of the three profiles and the interpretation of the depositional history in the Eger floodplain.
In: Zvara, Ema; Pejdanović, Snježana; Schneider, Birgit; Quante, Ella; Saeidi ghavi andam, Sara; Volosky, Diego; Lauer, Tobias; Fitzsimmons, Kathryn E; Marhan, Sven; Kandeler, Ellen; Poll, Christian; Oelmann, Yvonne; Neidhardt, Harald; Lindauer, Susanne; Friedrich, Ronny; Werther, Lukas; Frenzel, Peter; Kühn, Peter; Zielhofer, Christoph (2025): Multidisciplinary analyses of sediment-soil profiles from the Eger floodplain (Nördlingen, southern Germany) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972856